(3CfGLjd GdbjGeI GdoebOSIs
(3ChdgG (B:s
(3aGeG GdCMO YTQ GdJdejP aEfge PgHhG Edi GdLdjd Edi GdLHd MjK QSe dge GdjShY s
(3BNQgG (B:s
(3aPGHJ GdCee oJaJJ GdLHGdE QJaYJ GdTeS hbGe ddbeQ aj WbSg aj s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B175s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdcJH GdSeGhjIs